ANALISIS TATA KELOLA AIR(Studi Kasus Program Sumur Gali Pemerintah Desa Batnun, Kecamatan Amanuban Selatan, Kabupaten Timor Tengah Selatan) - Missa, Nofri Arwadi; Jacob, Ananias Riyoan Philip; Keon, Yohanes Fisher (SINERGI : Jurnal Riset Ilmiah, 2025)
Water management in Batnun Village is one example of where the government's dug well program has been implemented. However, an evaluation of the program's effectiveness is needed to understand the extent to which the dug well program has succeeded in distributing access to clean water in rural areas. Through a case study in Batnun Village, the author aims to examine how dug wells are managed in Batnun Village in providing clean water for the village community